PEMANFAATAN BUNGA ROSELLA MENJADI PEWARNA ALAMI PADA PEMBUATAN MIE KAYA ANTIOKSIDAN - Vitri Agustiarini; Marieska Verawaty; Laida Neti Mulyani; Viva Starlista (Jurnal Abdi Insani, 2023)
Rosella flowers contain anthocyanins which act as antioxidants. Anthocyanins in rosella flowers can be used as natural dyes. Utilization of natural dyes from rosella flowers is an option in the manufacture of functional food products, one of which is antioxidant-rich noodles. Roselle flower natural dyes besides being easy to obtain and cheap, this natural dye is not harmful to the body. The purpose of this activity is to increase the knowledge and skills of the people of Ulak Kerbau Baru Village, Tanjung Raja, by using rosella flowers as natural dyes for making antioxidant-rich noodles. The method of this activity uses observation, discussion, demonstrations and direct practice. Observation begins with permits, followed by a discussion of village potential and implementation of community service programs. The demonstration began with the provision of material related to the benefits of rosella flowers, noodle making training, business management training, and an introduction to noodle making equipment. Community service activities end with hands-on practice. Based on the results of community service activities, there was an increase in knowledge and skills related to the utilization of roselle flowers into antioxidant-rich noodles. Parameters that can be seen the increase is the average pretest value of 70 and posttest 92. The conclusion of this activity is an increase in community knowledge and skills in managing rosella flowers.